The efficacy and safety of complementary and alternative medicine in the treatment of nausea and vomiting during pregnancy: A systematic review and meta-analysis - Tan, Mo-Yao; Shu, Shi-Hong; Liu, Run-Lei; Zhao, Qian (Frontiers in Public Health, 2023)
Abstract Background: Complementary and alternative medicine (CAM) therapies are widely used for nausea and vomiting during pregnancy (NVP) due to the limitations of conventional medicine. However, their efficacy and safety remain controversial. Therefore, this meta-analysis was performed to assess the improvement of CAM therapy on NVP. Methods: Randomized controlled trials (RCTs) were searched for where the trial group was CAM and the control group was a conventional medicine or a placebo for NVP. This was done via 8 databases, including PubMed, EMBASE, the Cochrane Library, Web of Science, China National Knowledge Infrastructure, Wanfang, SinoMed, and VIP, from inception to October 25, 2022. The Stata 15.0 software was used to perform the meta-analysis. Results: 33 RCTs were included in this study. The acupuncture treatment was superior to conventional medicine at the effective rate [OR = 6.67, 95% CI (3.87, 11.51), P ≤ 0.001]. Ginger had a significant effect on conventional medicine at the Rhodes index [WMD = -0.42, 95% CI (-0.64, -0.20), P ≤ 0.001] and it has the same effect as drugs to relieve vomiting [SMD = 0.30, 95% CI (-0.12, 0.73), P = 0.160]. Compared with placebo, ginger had a higher effective rate [OR = 5.93, 95% CI (2.08, 16.88), P = 0.001], and lower Visual analog scale (VAS) of Nausea [WMD = -0.98, 95% CI (-1.57, -0.38), P = 0.001]. Ginger has the same antiemetic effect as placebo [WMD = 0.06, 95% CI (-0.14, 0.27), P = 0.544]. Acupressure was superior to conventional medicine at a dosage of antiemetic drugs [SMD = -0.44, 95% CI (-0.77, -0.11), P = 0.008], at the effective rate [OR = 5.82, 95% CI (2.81, 12.08), P ≤ 0.001]. Acupressure was superior to placebo at the effective rate [OR = 4.64, 95% CI (1.38, 15.58), P = 0.013]. Overall, CAM therapy is safer than conventional medicine or a placebo. Conclusion: The results showed that CAM therapies were able to alleviate NVP. However, due to the low quality of existing RCTs, more RCTs with large sample sizes are needed to validate this conclusion in the future.